Tumor protein expression of the DNA repair gene BRCA1 and lethal prostate cancer. (18th June 2020) - Stopsack, Konrad H; Gerke, Travis; Zareba, Piotr; Pettersson, Andreas; Chowdhury, Dipanjan; Ebot, Ericka M; Flavin, Richard; Finn, Stephen; Kantoff, Philip W; Stampfer, Meir J; Loda, Massimo; Fiorentino, Michelangelo; et al.
Abstract: DNA repair genes are commonly altered in metastatic prostate cancer, but BRCA1 mutations are rare. Preliminary studies suggest that higher tumor expression of the BRCA1 protein may be associated with worse prognosis. We undertook a prospective study among men with prostate cancer in the Health Professionals Follow-up Study and evaluated BRCA1 via immunohistochemical staining on tissue microarrays. BRCA1 was expressed in 60 of 589 tumors. Prevalence of BRCA1 positivity was 43% in the 14 men with metastases at diagnosis compared with 9% in non-metastatic tumors [difference, 33 percentage points; 95% confidence interval (CI), 7–59]. BRCA1-positive tumors had 2.16-fold higher Ki-67 proliferative indices (95% CI, 1.18–3.95), higher tumor aneuploidy as predicted from whole-transcriptome profiling, and higher Gleason scores. Among the 575 patients with non-metastatic disease at diagnosis, we evaluated the association between BRCA1 expression and development of lethal disease (metastasis or cancer-specific death, 69 events) during long-term follow-up (median, 18.3 years). A potential weak association of BRCA1 positivity with lethal disease (hazard ratio, 1.61; 95% CI, 0.82–3.15) was attenuated when adjusting for age, Gleason score and clinical stage (hazard ratio, 1.11; 95% CI, 0.54–2.29). In summary, BRCA1 protein expression is a feature of more proliferative and more aneuploid prostate tumors and is more common in metastatic disease. While not well suited as a prognostic biomarker in primary prostate cancer, BRCA1 protein expression may be most relevant in advanced disease. Abstract : This study reports that 10% of primary prostate cancers express the BRCA1 protein, especially more proliferative and aneuploid tumors. BRCA1 protein is not a suitable biomarker in primary disease and may be most relevant in metastatic prostate cancer.